Beban Kerja, Tingkat Kepuasan Karyawan, Dan Tingkat Loyalitas Karyawan Pengaruhnya Terhadap Kinerja Karyawan Kontrak Di Dinas Sosial Kota Denpasar - Lusia Vreyda Adveni; Luh Kadek Budi Martini; Ni Kadek Windi Randiani (Journal Research of Management, 2024)
This study aims to determine: (1) The effect of workload on the performance of contract employees at the Denpasar City Social Service, (2) The effect of employee satisfaction level on the performance of contract employees at the Denpasar City Social Service, (3) The effect of employee loyalty level on the performance of contract employees at the Denpasar City Social Service, (4) The effect of workload, employee satisfaction level, and employee loyalty level on the performance of contract employees at the Denpasar City Social Service. This research is a descriptive analysis research with quantitative methods. Data collection with a Likert scale questionnaire. Data analysis using multiple linear regression analysis and hypothesis testing with the T test and F test. The sample in this study were 74 contract employees of the Denpasar City Social Service. The results of the study found that: (1) Workload has a positive and significant effect on employee performance with a significance value of 0.001 <0.05 and a t-count of 3.395. (2) The level of employee satisfaction has a positive and significant effect on employee performance with a significance value of 0.001 <0.05 and a t-count of 3.389. (3) Employee loyalty level has a positive and significant effect on employee performance with a significance value of 0.001 < 0.05 and a t-count of 3.531. (4) Workload, employee satisfaction level, and employee loyalty level have a positive and significant effect on contract employee performance with a significance value of 0.000 < 0.05 and an f-count of 30, 738.